2015
DOI: 10.1038/ncomms6703
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical densification and negative thermal expansion in Ce-based metallic glass under high pressure

Abstract: The polyamorphsim in amorphous materials is one of the most fascinating topics in condensed matter physics. In amorphous metals, the nature of polyamorphic transformation is poorly understood. Here we investigate the structural evolution of a Ce-based metallic glass (MG) with pressure at room temperature (RT) and near the glass transition temperature by synchrotron X-ray diffraction, uncovering novel behaviours. The MG shows hierarchical densification processes at both temperatures, arising from the hierarchy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…Secondly, the temperature of our study is relatively lower (by 50 degrees), say not as close to T g as in the Luo et al study. However, the present work does not clearly discriminate a possible weak first-order nature as argued in Ref [19]. The discontinuous volume change measured in our work between 4 and 6…”
Section: Polyamorphism Of Cerium-mg At High Pressurecontrasting
confidence: 44%
See 4 more Smart Citations
“…Secondly, the temperature of our study is relatively lower (by 50 degrees), say not as close to T g as in the Luo et al study. However, the present work does not clearly discriminate a possible weak first-order nature as argued in Ref [19]. The discontinuous volume change measured in our work between 4 and 6…”
Section: Polyamorphism Of Cerium-mg At High Pressurecontrasting
confidence: 44%
“…Also using x-ray techniques, Duarte et al [15] reported a low-and high-density amorphous phases at different pressure ranges, with the occurrence of a hysteresis at the transition, and of an intermediate density region expected to coincide with a mixture of both phases, or with a new metastable phase. This last hypothesis has been recently reported by Luo et al [19], through an exploration of the LDA-HDA transformation path at the temperature of 390 K.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations